A generator of peroxynitrite activatable with red light. Issue 13 (11th March 2021) - Parisi, Cristina; Failla, Mariacristina; Fraix, Aurore; Menilli, Luca; Moret, Francesca; Reddi, Elena; Rolando, Barbara; Spyrakis, Francesca; Lazzarato, Loretta; Fruttero, Roberta; Gasco, Alberto; Sortino, Salvatore
Abstract : Excitation of a molecular hybrid with highly biocompatible red light generates cytotoxic peroxynitrite, produces red fluorescence useful for cell tracking and induces remarkable cancer cell death at very low concentrations and very low light doses. Abstract : The generation of reactive oxygen species (ROS) and reactive nitrogen species (RNS) as "unconventional" therapeutics with precise spatiotemporal control by using light stimuli may open entirely new horizons for innovative therapeutic modalities. Among ROS and RNS, peroxynitrite (ONOO − ) plays a dominant role in chemistry and biology in view of its potent oxidizing power and cytotoxic action. We have designed and synthesized a molecular hybrid based on benzophenothiazine as a red light-harvesting antenna joined to an N -nitroso appendage through a flexible spacer. Single photon red light excitation of this molecular construct triggers the release of nitric oxide (˙NO) and simultaneously produces superoxide anions (O2 ˙ − ). The diffusion-controlled reaction between these two radical species generates ONOO −, as confirmed by the use of fluorescein-boronate as a highly selective chemical probe. Besides, the red fluorescence of the hybrid allows its tracking in different types of cancer cells where it is well-tolerated in the dark but induces remarkable cell mortality under irradiation with red light in a very low concentration range, with very low light doses ( ca. 1 J cm −2 ). This ONOO − generator activatable by highly biocompatible and tissue penetrating single photon red light can open up intriguing prospects in biomedical research, where precise and spatiotemporally controlled concentrations of ONOO − are required.